Prevalence of sensorineural hearing loss in patients with Diabetes Mellitus - Sameer Karmacharya; Ashish Dhakal; Santosh Kumar Sah (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Various kinds of auditory involvement are reported in diabetic subjects. One of them is that of gradual onset of bilateral sensorineural deafness, involving mainly higher frequencies in elderly patients. This study was aimed to access the prevalence of sensorineural hearing loss (SNHL) in a patient with Diabetes Mellitus and its relation to age, sex, duration of DM, and control of DM. Results: Diabetic patients had insidious onset, gradually progressive, bilaterally symmetrical SNHL. SNHL is prevalent in 72% of type 2 diabetes patients compared to 18% of controls. It is correlated with the increasing age and duration of diabetes. Poor control of diabetes showed an increased prevalence of SNHL compared to good control of diabetes. Conclusion: There was an increased prevalence of SNHL in type 2 diabetes patients and it is more evident in patients with long duration of diabetes and more pronounced in patients with poor diabetic control.